Fenitrothion-Induced Structural and Functional Perturbations in the Yolk Lipoproteins of the Shrimp Macrobrachium borellii - García, Carlos Fernando (2004)
Two lipovitellin (LV) forms containing the same apoproteins but differing in their lipid composition were isolated from Macrobrachium borelii eggs at early (LVe) and late (LVI) embryogenic stages and characterized. These two forms of LV, as well as liposomes prepared with lipids extracted from them, were used as simpler models to study the effect of the pesticide fenitrothion (FS) on their structures and functions. Rotational diffusion and fluorescence lifetime of two fluorescent probes [1,6-diphenyl-1,3,5-hexatriene (DPH) and 3-(p-(6-phenyl)-1,3,5-hexatrienal)phenylpropionic acid (DPH-PA)] were used to obtain information on structural changes induced by FS in the inner and outer regions of the LV, respectively. Comparison of the rotational behavior of these probes in native LV and liposomes (LP) from extracted LV lipids suggests that apoprotein-lipid interactions result in an ordered neutral lipid core. FS increased the lipid phase polarity of both LV and LP forms. The rotation of these probes in LP was not affected, suggesting a dependence of FS action on lipid-protein interactions. DPH-PA steady-state anisotropy showed that, unlike the LVe form, the LVI form was sensitive to extremely low FS concentrations. The ability of both LV to transfer palmitic acid to albumin was increased, but in a dissimilar manner, by the presence of FS. Such differences in the sensitivity of the LV at different steps of embryogenesis to FS influence the toxic action of this insecticide.